ChemInform Abstract: Shape‐Controlled Synthesis of MnWO4 Nanocrystals via a Simple Hydrothermal Method. Issue 44 (14th October 2013) - Yang, Linlin; Wang, Yonggang; Wang, Yujiang; Wang, Xiaofeng; Wang, Lijian; Han, Gaorong
Abstract The nanocrystals of title are prepared at different pH values by hydrothermal reaction of Na2WO4 and either MnCl2, MnCO3, or Mn(OH)2 as Mn source (autoclave, 150 °C, 3 h).